2020
DOI: 10.1111/1365-2745.13379
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of global change factors on terrestrial net primary productivity are treatment length and intensity dependent

Abstract: Individual effects of co‐occurring global change factors on net primary productivity (NPP) have been widely studied; however, their interactive effects remain highly debated. Here, we conducted a global meta‐analysis based on 919 multifactor observations from 120 published studies to examine the interactive effects on NPP of global change factors including elevated [CO2], warming, nitrogen addition, irrigation, drought and changes in species diversity. On average, of the factors studied, six pairs of factors h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 60 publications
(98 reference statements)
2
23
0
Order By: Relevance
“…Thus, although longer durations of PPT anomalies can increasingly impact ecosystem structure and functioning, studies indicate this response is not consistent and can be either muted or nonlinear and thus change through time (Barbeta et al, 2013; Goulden & Bales, 2019; Ma et al, 2020; Peters et al, 2014). Important community‐level dynamics occurring during an event are difficult to predict a priori and may arise after a single growing season (Felton, Zavislan‐Pullaro, et al, 2019), multiple years (Evans et al, 2011; Griffin‐Nolan et al, 2019; Hoover et al, 2014b), or only after a decade of PPT change (Collins et al, 2012).…”
Section: A Role For the Duration Of Precipitation Anomaliesmentioning
confidence: 99%
“…Thus, although longer durations of PPT anomalies can increasingly impact ecosystem structure and functioning, studies indicate this response is not consistent and can be either muted or nonlinear and thus change through time (Barbeta et al, 2013; Goulden & Bales, 2019; Ma et al, 2020; Peters et al, 2014). Important community‐level dynamics occurring during an event are difficult to predict a priori and may arise after a single growing season (Felton, Zavislan‐Pullaro, et al, 2019), multiple years (Evans et al, 2011; Griffin‐Nolan et al, 2019; Hoover et al, 2014b), or only after a decade of PPT change (Collins et al, 2012).…”
Section: A Role For the Duration Of Precipitation Anomaliesmentioning
confidence: 99%
“…Among them are variation in the magnitude of precipitation events, such as dry and wet years, experienced by any particular system (Knapp et al, 2017b;Petrie et al, 2018;Wu et al, 2018;Felton et al, 2019), inherent differences in the assembly of the local plant community (Byrne et al, 2017;Mulhouse et al, 2017;Sternberg et al, 2017), and disturbance-induced alterations to abiotic properties (e.g., soil moisture and nutrients Willms et al, 1986;Willms et al, 1993). However, evidence indicates that the sensitivity of ecosystem functions (e.g., ANPP) to climate change may not represent simple additive responses to multiple environmental factors (Felton et al, 2020;Ma et al, 2020). This suggests that our ability to project ecosystem sensitivity to predicted changes in precipitation variability is hindered by a limited understanding of combined factors, which in grasslands will be the by-product of inter-annual variability in precipitation coupled with grazing.…”
Section: Introductionmentioning
confidence: 99%
“…However, much of current understanding of ecosystem sensitivity to precipitation variability is derived from responses of above‐ground net primary productivity (ANPP) to precipitation (Knapp et al, 2017b) and assessed independently of grazing effects (but see Irisarri et al, 2016), despite grazing being the predominant land‐use of grasslands (Asner et al, 2004). As such, understanding ecosystem responses to the interactive effects of co‐occurring factors is critical, and a reliable benchmark is needed for predicting ecosystem sensitivity robustly from ecosystem models (Dangal et al, 2017; Chen et al, 2018; Ma et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Results from a large number of primarily temperate experiments and from observational studies across temperate and tropical temperature gradients clearly show that in the absence of moisture limitations to productivity, warming stimulates the flux of C into and the loss of C from ecosystems (Berryman et al, 2016; Bond‐Lamberty et al, 2018; Bond‐Lamberty & Thomson, 2010; Gherardi & Sala, 2020; Giardina et al, 2014; Litton & Giardina, 2008; Litton et al, 2011; Luyssaert et al, 2007; Melillo et al, 2016; Sistla et al, 2013). While the impacts of rising temperatures on belowground process rates have received increasing attention (Bradford et al, 2016; Caprez et al, 2012; Fissore et al, 2013; Ziegler et al, 2017), including in tropical systems (Giardina et al, 2014; Nottingham et al, 2020; Wood et al, 2012; Wood et al, 2019), the drivers of these fluxes, in particular the interactive effects of warming and interannual variation in rainfall, remain understudied (Ma et al, 2020; Piao et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Research directed at understanding whole stand responses to multiple climate change variables is limited. In a meta‐analysis of 120 mostly temperate experimental studies manipulating temperature and moisture, NPP decreased with warming while synergistic interactions disappeared at the highest temperatures (Ma et al, 2020). In a grassland study, Reich et al (2020) found negative effects of reduced moisture on productivity, but positive effects of elevated temperature, moisture, CO 2 , and nitrogen.…”
Section: Introductionmentioning
confidence: 99%